(untitled) - J.K.Rowling (London Bloomsbury Publishing, 2014)
The fifth adventure in the spellbinding Harry Potter saga - the series that changed the world of books forever Dark times have come to Hogwarts. After the Dementors' attack on his cousin Dudley, Harry Potter knows that Voldemort will stop at nothing to find him. There are many who deny the Dark Lord's return, but Harry is not alone: a secret order gathers at Grimmauld Place to fight against the Dark forces. Harry must allow Professor Snape to teach him how to protect himself from Voldemort's savage assaults on his mind. But they are growing stronger by the day and Harry is running out of time. These classic editions of J.K. Rowling's internationally bestselling, multi-award-winning series feature thrilling jackets by Jonny Duddle, bringing Harry Potter to the next generation of young readers. It's time to PASS THE MAGIC ON ...
Keywords: Young Adult; Fantasy; Fiction; Magic; Childrens; Adventure; Classics; Science Fiction